Pedagogy for Interdisciplinary Habits of Mind - Luckie, Douglas; Newell, William (Journal of Interdisciplinary Studies in Education, 2019)
Over the years, there has been little attempt made to collect, organize, and codify either the interdisciplinary habits of mind or the pedagogies used to promote them. Teaching interdisciplinary courses requires instilling interdisciplinary habits of mind by using strategies for active learning and reflective liberal thinking. This publication emerged from discussions and surveys used to evaluate interdisciplinary habits of mind and pedagogies which focused on four categories: drawing, modifying, integrating, and evaluating insights drawn from different disciplines. Prior to face-to-face discussions, surveys were sent to 75 expert faculty who had great experience teaching IDS courses. The survey and follow-up discussion examined the four categories of habits of mind one by one, identifying pedagogies useful in promoting any or all of the habits of mind within each category, and how each pedagogy works to clarify how it produces such habits of mind. The breakout discussions were observed, transcribed, and analyzed throughout the meetings. After analysis, the authors came to three conclusive inferences: (1) Course organization and structure have an important albeit indirect effect on pedagogy, (2) traditional pedagogies have an important role to play in teaching interdisciplinary courses, and (3) active learning is especially important in interdisciplinary pedagogy, not just a supplement.